Impact on Patient Care of a Multidisciplinary Center Specializing in Colorectal and Pelvic Reconstruction - Vilanova-Sánchez, Alejandra; Reck, Carlos Albert; Wood, Richard J.; Garcia Mauriño, Cristina; Gasior, Alessandra C.; Dyckes, Robert E.; McCracken, Katherine; Weaver, Laura; Halleran, Devin R.; Diefenbach, Karen; Minzler, Dennis; Rentea, Rebecca M.; et al. (Frontiers in Surgery, 2018)
Aim of the study Many patients with an anorectal malformation (ARM) or pelvic anomaly have associated urologic or gynecologic problems. We hypothesized that our multidisciplinary center, which integrates pediatric colorectal, urologic, gynecologic and GI motility services, could impact a patient’s anesthetic exposures and hospital visits. Methods We tabulated during 2015 anesthetic/surgical events, endotracheal intubations, and clinic/hospital visits for all patients having a combined procedure. Main results 82 patients underwent 132 combined procedures (table 1). The median age at intervention was 3 years [0.2-17], and length of follow up was 25 months[7-31]. The number of procedures in patients who underwent combined surgery was lower as compared to if they had been done independently [1(1-5) vs 3(2-7)(p<0.001)]. Intubations were also lower (1[1-3]vs2[1-6]; p<0.001). Hospital length of stay was significantly lower for the combined procedures vs the theoretical individual procedures (8 days [3-20]vs 10 days [4-16]) p<0.05). Postoperative clinic visits were fewer when combined visits were coordinated as compared to the theoretical individual clinic visits (urology, gynecology and colorectal) (1[1-4] vs 2[1-6]; p=<0.001). Conclusion Patients with anorectal and pelvic malformations are likely to have many medical or surgical interventions during their lifetime. A multidisciplinary approach can reduce surgical interventions, anesthetic procedures, endotracheal intubations, and hospital/outpatient visits. Key Words: Multidisciplinary approach, colorectal surgery, centralization of care, anorectal malformations, Hirschsprung disease, pelvic reconstruction